Comprehensive Insights into Mechanisms for Ventricular Remodeling in Right Heart Failure - Dongmei Jiang; Jie Wang; Rui Wang; Yun Wu (Reviews in Cardiovascular Medicine)
Ventricular remodeling in right heart failure is a complex pathological process involving interactions between multiple mechanisms. Overactivation of the neuro-hormonal pathways, activation of the oxidative stress response, expression of cytokines, apoptosis of cardiomyocytes, and alterations of the extracellular matrix (ECM) are among the major mechanisms involved in the development of ventricular remodeling in right heart failure. These mechanisms are involved in ventricular remodeling, such as myocardial hypertrophy and fibrosis, leading to the deterioration of myocardial systolic and diastolic function. A deeper understanding of these mechanisms can help develop more effective therapeutic strategies in patients with right heart failure (RHF) to improve patient survival and quality of life. Despite the importance of ventricular remodeling in RHF, there are a limited number of studies in this field. This article explores in-depth historical and current information about the specific mechanisms in ventricular remodeling in RHF, providing a theoretical rationale for recognizing its importance in health and disease.